Ultrasonographic assessment of right internal jugular vein dimensions following passive legs elevation versus hepatic compression: a cross-sectional study - Ashok Gautam; Balkrishna Bhattarai; Ashish Ghimire; Jagat Narayan Prasad; Parineeta Thapa; Yogesh Dhakal (BMC Anesthesiology)
Abstract Background Central vein cannulation is a common invasive procedure performed in critically ill patients and during major surgeries. This study compares the right internal jugular vein’s diameters and cross-sectional area after passive legs elevation and hepatic compression, analyzing these based on age, gender, body mass index and fasting duration. Methods A cross-sectional study of 184 elective surgery patients (84 males, 84 females) at B.P. Koirala Institute of Health Sciences, Nepal, included 18–75 years. Exclusions: patients on mechanical ventilation, history of right jugular cannulation, neck/abdominal swelling, raised intracranial pressure, lower extremity fracture and refusal of consent. Age, gender, fasting duration and body mass index were recorded. The 6–13 MHz linear probe identified the internal jugular vein by its compressibility and anechoic appearance. Short axis view of transverse and anteroposterior diameters and cross-sectional area were measured in short axis view at the cricoid level using electronic calipers. Maximum diameter and average cross-sectional area were measured in supine with the head rotated 15°- 30° left, after one minute of passive legs elevation at 45° and after hepatic compression for one minute with a 19.6 N force. Results Hepatic compression increased transverse diameter by 1.64 (0.40) cm, p = 0.035 and cross-sectional area by 1.28 (0.54) cm2, p = 0.047. No gender differences were noted. The transverse diameter increased in underweight (p = 0.02) and overweight (p = 0.01) patients. The cross-sectional area increased in overweight (p = 0.03). Passive legs elevation matched hepatic compression for the fasting durations. Conclusion Hepatic compression better optimizes transverse diameter and cross-sectional area of right internal jugular vein than passive legs elevation.